PENGELOLAAN KAWASAN KARST Dl KALIMANTAN TIMUR - Sugiyanto, Bambang (Naditira Widya, 2008)
There are still some flaws in cultural resource management in Indonesia, especially in regard to cultural heritage management in karst environment. It is necessary to establish a good coordination and cooperation on archaeological resource management in the karst environment between the departments and district governments of: Culture and Tourism, Forestry, Environment, Mineral and Energy. A excellent system of coordination and cooperation in respect to archaeological resource management in karst environment is well represented in East Kalimantan.